2020
DOI: 10.1039/d0ra07360a
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-free regioselective acetylation of primary hydroxy groups in partially protected and unprotected thioglycosides with acetic acid

Abstract: Highly regioselective acetylation of primary hydroxy groups in thioglycoside derivatives was achieved by treatment with aqueous or anhydrous acetic acid (60–100%) at elevated temperatures (80–118 °C), avoiding manipulations with protective groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…A similar situation was observed in case of ethyl 6‐ O ‐acetyl‐1‐thio‐α‐ d ‐galactopyranoside ( 10 ) with electron withdrawing acetyl substituent at O‐6, which was obtained recently by us by regioselective acetylation of diol 9 using aqueous acetic acid [13] . After the treatment of compound 10 with anhydrous TFA in CH 2 Cl 2 at 0 °C (method B ), a mixture of furanosides 12 along with unreacted starting material 10 was detected by NMR (Table 3, entry 6).…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…A similar situation was observed in case of ethyl 6‐ O ‐acetyl‐1‐thio‐α‐ d ‐galactopyranoside ( 10 ) with electron withdrawing acetyl substituent at O‐6, which was obtained recently by us by regioselective acetylation of diol 9 using aqueous acetic acid [13] . After the treatment of compound 10 with anhydrous TFA in CH 2 Cl 2 at 0 °C (method B ), a mixture of furanosides 12 along with unreacted starting material 10 was detected by NMR (Table 3, entry 6).…”
Section: Resultssupporting
confidence: 76%
“…Earlier we reported that the cleavage of 4,6‐ O ‐benzylidene group in ethyl 1‐thio‐β‐ d ‐galactopyranoside with TIPS groups at O‐2 and O‐3 (compound 1 , Figure 1) with aq TFA in CH 2 Cl 2 (method A ) gave the corresponding 1‐thio‐β‐ d ‐galactofuranoside 5 in 76 % yield (Table 2, entry 1) [12] . During the reaction of isomeric ethyl 4,6‐ O ‐benzylidene 2,3‐di‐ O ‐TIPS‐1‐thio‐α‐ d ‐galactofuranoside ( 2 ) [13] with α‐configuration under identical conditions (method A ) the formation of 1‐thio‐α‐ d ‐galactofuranoside 6 with TIPS groups at O‐2 and O‐3 and α‐configured diol 4 in pyranose form (Table 2, entry 2) was observed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations